Introduction. “Victorians Like US”: The Victorian Age Revisited - Silva, Elisabete Mendes (2022)
“Victorians Like Us” was a project carried out by the English Culture Research Group of The University of Lisbon Centre for English Studies. The four conferences organised between 2012 and 2018 and held at the Faculty of Arts and Humanities in Lisbon gave visibility to the project. They all promoted discussion on a wide variety of topics pertaining to ideological, social, and cultural settings and encompassing all facets of the Victorian era. The topics fostered a critical and creative dialogue on Victorianism and our current age. This introduction first sets the context for the present issue of Anglo-Saxonica, which comprises expanded versions of papers delivered at the Victorians Like Us III conference, and then briefly describes their main topics and goals.